Grow Now, Clean Later: Evidence from South Asian Countries - K.C., Subin (Economic Journal of Nepal, 2023)
The environmental Kuznet curve (EKC) postulates an inverted U-shaped relationship between economic growth and environmental degradation, suggesting that as economies develop, environmental quality initially worsens before improving. The study aims to check whether South Asian countries follow the EKC hypothesis or not and also check the pattern of the EKC. Although this study confirms the traditional understanding of the EKC, it also identifies an alternative perspective suggesting an N-shaped trajectory for the EKC. Through an empirical analysis, this paper finds evidence supporting this N-shaped pattern, indicating a transition from degradation to improvement as economies progress. The findings have significant implications for policy makers and environmental advocates, highlighting the need for proactive measures to accelerate the transition toward sustainable development. Additionally, this emphasizes the importance of designing effective environmental policies, encouraging investments in clean technologies, and recognizing regional variations in the turning point of the N-shaped curve. Further research, including case studies and comparative analysis, is warranted to deepen our understanding of this relationship and facilitate informed decision making towards a more sustainable and resilient future.